Practical Assessment Scheme to Service Selection for SOC-based Applications - Garriga, Martín (2011)
Service-Oriented Computing promotes building applications by consuming reusable services. However, facing the selection of adequate services for a specific application still is a major challenge. Even with a reduced set of candidate services, the assessment effort could be overwhelming. On a previous work we have presented a novel approach to assist developers on discovery, selection and integration of services. This paper presents the selection method, which is based on a comprehensive scheme for services’ interfaces compatibility. The scheme allows developers to gain knowledge on likely services’ interactions and their required adaptations to achieve a positive integration. The scheme is also complemented by a framework based on black-box testing to verify compatibility on the expected behavior of a candidate service. The usefulness of the selection method is highlighted through a series of case studies.